Sorption capacity and fate of sulfadiazine in soils with different pedological properties - dos Santos, F. F.; Filho, W. B.F.; Paulino, A. T.; Rosa, A. H. [UNESP] (My University, 2024)
Sulfadiazine is a drug used for treating diseases in animals/humans and controlling pests in agricultural crops. High doses ingested by living beings are excreted by feces and urine due to incomplete metabolization. High doses can also enter the environment after agricultural applications. As the fate of many chemotherapies in the environment remains unknown in several places, the aim of this work was to determine the sorption capacity and mechanism of sulfadiazine in humic gley (S1), red, yellow podzolic (S2) and hydromorphic (S3) soils with different pedological properties to improve the understanding of environmental pollution by sulfonamides. Samples of the S1, S2 and S3 soils were collected from areas without anthropological activities at a depth of 10 cm for pedological characterization. These samples were then employed in sulfadiazine sorption studies at different soil/solution ratios, pH (3.5 and 5.5) and initial drug concentrations (0.5, 1.0, 2.0, 3.0, 4.0 and 5.0 mg L−1). Higher OM and clay contents were determined in the S1 soil compared to the S3 and S2 soils (S1 > S3 > S2). Similar results were found for the cation exchange capacity (CEC). Two-parameter isotherm models determined that sulfadiazine sorption efficiency was higher in S1 than S3 and S2, confirming the pedological properties. The Freundlich constant (Kf) was 2.96, 2.52 and 1.50 for sorption in S1, S3 and S2, respectively, whereas the sorption constant (Kd) was 6.60, 2.50 and 1.70, respectively, at pH 3.5. These results were similar for both pH values, except pH 5.5 using S3, for which higher Kf, Kd and K oc values were found. No effective sulfadiazine sorption was found in calcinated soil, indicating weaker intermolecular interactions between sulfadiazine and soil due probably to change in charge on sorbent and sorbate structures. This increases the leaching process, facilitating the transport of pollutants into water, soil and sediment.
Keywords: Drug; Emerging pollutant; Soil; Sorption; Sulfadiazine